Calcified carotid artery atheroma on standard dental radiographs: A public health opportunity for cardiovascular risk reduction - Vicky Mai; Aneesha Taneja; Hannu Larjava; Babak Chehroudi; David MacDonald; Christina Luong (Elsevier, 2024)
Objective: Calcified carotid artery atheroma (CCAA) can be identified incidentally on standard dental panoramic radiographs (DPRs). We sought to (1) determine the prevalence of CCAA on DPRs in a general dental population and (2) establish the proportion of patients in whom this would represent a new statin-indicated condition. Methods: We identified patients aged ≥30 with DPRs from 2019 to 2021 from the University of British Columbia Dental Clinic. Patient charts were reviewed for use of lipid-lowering therapies (LLT) and existing statin-indicated conditions. DPRs for each patient were evaluated for the presence and characteristics of CCAA. Results: Of 921 patients with a DPR and documented medical history, 548 (59.5 %) were diagnostic for evaluation of CCAA. Although 116/548 (21.2 %) of these patients had evidence of CCAA, only 25.9 % (30/116) were already on LLT; another 20.7 % (24/116) of patients with CCAA had a pre-existing statin-indicated condition but were not on LLT. Therefore, in 53.4 % (62/116) of patients with CCAA-positive DPRs, this constituted a new diagnosis of atherosclerosis not yet treated with LLT, representing 6.7 % (62/921) of the clinic population and 11.3 % of individuals with DPRs of diagnostic quality (62/548). Dyslipidemia, hypertension, coronary artery disease, diabetes, atrial fibrillation, stroke/transient ischemic attack, older age, and male sex were all found to be significant predictors of CCAA. Conclusion: CCAA is a common finding among patients with DPRs and in over half of cases, the presence of CCAA represents a new diagnosis of atherosclerosis. The high prevalence of new, untreated atherosclerosis in this population indicates an opportunity for risk factor modification and collaboration between dentists and physicians to optimize patient care.